MEMBANGUN SPIRIT KEWIRAUSAHAAN SEBAGAI LANGKAH POSITIF DI MASA PANDEMI PADA KELOMPOK PKK KEL. CIPINANG MELAYU - Apriansyah, Muger; Sahroni, Sahroni; Sutoro, Moh.; Mukrodi, Mukrodi; Krisyanto, Edy (LPPM Universitas Pamulang, 2020)
This community service aims to foster entrepreneurship spirit the pandemic situation in PKK Kel. Cipinang Melayu group. As the things Issues raised how to start a business with good managemen. The method used in the implementation of this service is carried out in several activities, namely (a). The Preparation Phase includes: (1). Initial survey (2) Consolidation and determination of target locations, (3). Preparation to sosialitations of materials / materials. The results of this activity can later be beneficial for to PKK Kel. Cipinang Melayu group, in starting entrepreneurship with a good mangement approach in a pandemic situation.